Code-Switching as a Bridge to Language Acquisition: An Autoethnography of a Multilingual Journey - Celiacika Gustisiwi Puteri (Balai Bahasa Provinsi Bali, 2025)
This autoethnographic study aims to explore the role of code-switching as a language acquisition and self-discovery strategy within an English language learner’s journey. This research integrates personal narrative and reflection to analyze the author’s own linguistic experiences. The research data was gathered through retrospection, narrative journaling, and an analysis of personal linguistic interactions. The data was then thematically analyzed to identify emerging patterns and meanings in the use of code-switching, connecting them to the processes of language acquisition and identity formation. The findings indicate that code-switching serves not only as a functional tool but also as an adaptive mechanism that facilitates cognitive and cultural understanding. This process highlights how multilingualism can be leveraged to transcend monolingual limitations, leading to a deeper mastery of the language and a richer sense of self. AbstrakPenelitian autoetnografi ini bertujuan untuk mengeksplorasi peran alih kode sebagai strategi akuisisi bahasa dan penemuan diri dalam perjalanan seorang pembelajar bahasa Inggris. Studi ini mengintegrasikan narasi pribadi dan refleksi untuk menganalisis pengalaman linguistik penulis. Data penelitian dikumpulkan melalui retrospeksi, jurnal naratif, dan analisis interaksi linguistik pribadi. Data kemudian dianalisis secara tematis untuk mengidentifikasi pola dan makna yang muncul dari penggunaan alih kode, menghubungkannya dengan proses akuisisi bahasa dan pembentukan identitas. Hasil penelitian menunjukkan bahwa alih kode berfungsi bukan hanya sebagai alat fungsional, tetapi juga sebagai mekanisme adaptif yang memfasilitasi pemahaman kognitif dan budaya. Proses ini menyoroti bagaimana multibahasa dapat dimanfaatkan untuk melampaui batasan monolingual, yang mengarah pada penguasaan bahasa yang lebih mendalam dan pemahaman diri yang lebih kaya.